EPILEPSY ASSOCIATED WITH EPILEPTIC EYELID MYOCLONIA WITH OR WITHOUT ABSENCES - M. B. Mironov; M. Yu. Bobylova; M. O. Abramov; T. M. Krasilshchikova; A. N. Zavadenko; I. O. Shchederkina; А. S. Petrukhin (Эпилепсия и пароксизмальные состояния)
Epileptic eyelid myoclonia with or without absences  – epileptic seizures  presented  with closing of eyes  and frequent (3-6 times  per second)  rhythmic  myoclonias  of eyelids («eyelid fluttering»). They can be accompanied  by absences seizures  of short duration or they are not accompanied  by loss of consciousness. We analyzed the forms of epilepsy, seizure types and compulsive  movements of eyes associated with epileptic eyelid myoclonia. We present an algorithm of video-EEG monitoring to diagnostic this epileptic syndrome.  Epileptic eyelid myocloniais a seldom type of seizures. It observed with generalized and focal epilepsies. Epileptic eyelid myoclonia can be combined with It can be combined with obsessive eye movementsб what is need differential diagnosis with tics and other obsessions. Using of prolong EEG monitoring is necessary  in order to avoid the deterioration of the state of imaginary or perceived improvement. AEP efficiency depends  on the epileptic syndrome  associated with of еpileptic eyelid myoclonia.